CREATION OF FEMALE POETS IN THE KOKAN LITERARY ENVIRONMENT - Omonova Durdona; Scientific Supervisor: Omanova Mubora (Galaxy International Interdisciplinary Research Journal, 2024)
The article provides information about the formation of the Kokan literary environment, the life and work of poets who worked in the palace during the reign of Amir Umar Khan. Excerpts from works describing their life in the palace and their place in cultural life were interpreted. Some aspects of poets lyrics were analyzed.